BASKETBALL AS CONTENT DEVELOPMENT OF MULTIPLE INTELLIGENCES (Fiep Bulletin - online, 2013)
The modern basketball has become one of the most played team sports in the world, both in formal educational environments as in non-formal settings, this sport draws attention due to its aspects of strength and speed and because of his movements that encompass a broad collection skills. There are numerous possibilities that basketball practice can offer to fellow practitioner. Inserted these possibilities, multiple intelligences stand up simultaneously with developing skills directed to this sport in view of the relationship between the movements performed during the match witnessed situations in times of practice and games in the initiation of the eight high-yield Gardner's intelligences linked to each other and bring the sport, social and individual values ??important for human development. Thus, the vocation of this essay is to analyze theoretically the possibility of using basketball as a means to develop the multiple intelligences and values ??linked to sport in formal and non-formal systems of education. We hope that our positions are shared, challenged or enriched.
Keywords: Multiple Intelligences; Basketball; Values??.